Women Empowerment Through Entrepreneurship - Mishra, Shila (GS WOW: Wisdom of Worthy Research Journal, 2025)
With view to foster sustainable economic operations in Nepal, contributions from both men and women are essential , particularly as the country advances its entrepreneurial culture. The research is a review based research theoretical review, empirical review, contextual review and policy review were done in a systemetic manner. Context-dependent pathways financial acumen transcends venture launch, enabling resilient decision-making and Nepal’s economic uncertainty were emphasized. Preliminary synthesis reveals financial literacy and adaptive behaviors as pivotal for opportunity recognition and autonomy motives, fostering distinct entrepreneurial typologies. Women has huge potential and empathetic capacity which ensures them that their involvement in business not only focus to make millions , but help billions which resulted into excellency of sustanable business operation either pioneers, guardians, drivers or integrators for prospority of the society through balanced business chemistry